STAT5 is activated in macrophages by breast cancer cell-derived factors and regulates macrophage function in the tumor microenvironment - Emily A. Jesser (BMC, 2021)
Abstract Background In breast cancer, complex interactions between tumor cells and cells within the surrounding stroma, such as macrophages, are critical for tumor growth, progression, and therapeutic response. Recent studies have highlighted the complex nature and heterogeneous populations of macrophages associated with both tumor-promoting and tumor-inhibiting phenotypes. Defining the pathways that drive macrophage function is important for understanding their complex phenotypes within the tumor microenvironment. Signal transducer and activator of transcription (STAT) transcription factors, such as STAT5, are key regulators of immune cell function. The studies described here investigate the functional contributions of STAT5 to tumor-associated macrophage function in breast cancer. Methods Initial studies were performed using a panel of human breast cancer and mouse mammary tumor cell lines to determine the ability of tumor cell-derived factors to induce STAT5 activation in macrophages. Further studies used these models to identify soluble factors that activate STAT5 in macrophages. To delineate STAT5-specific contributions to macrophage function, a conditional model of myeloid STAT5 deletion was used for in vitro, RNA-sequencing, and in vivo studies. The effects of STAT5 deletion in macrophages on tumor cell migration and metastasis were evaluated using in vitro co-culture migration assays and an in vivo tumor cell-macrophage co-injection model. Results We demonstrate here that STAT5 is robustly activated in macrophages by tumor cell-derived factors and that GM-CSF is a key cytokine stimulating this pathway. The analysis of RNA-seq studies reveals that STAT5 promotes expression of immune stimulatory genes in macrophages and that loss of STAT5 in macrophages results in increased expression of tissue remodeling factors. Finally, we demonstrate that loss of STAT5 in macrophages promotes tumor cell migration in vitro and mammary tumor metastasis in vivo. Conclusions Breast cancer cells produce soluble factors, such as GM-CSF, that activate the STAT5 pathway in macrophages and drive expression of inflammatory factors. STAT5 deletion in myeloid cells enhances metastasis, suggesting that STAT5 activation in tumor-associated macrophages protects against tumor progression. Understanding mechanisms that drive macrophage function in the tumor microenvironment will ultimately lead to new approaches that suppress tumor-promoting functions while enhancing their anti-tumor functions.